PERTUMBUHAN DAN PRODUKSI TEBU (SACCHARUM OFFICINARUM; POACEAE) PADA BERBAGAI PAKET PEMUPUKAN DI LAHAN KERING BERPASIR - Supriyadi, Supriyadi; Diana, Nunik Eka; Djumali, Djumali (Research Center for Biology-Indonesian Institute of Sciences, 2018)
Improvement of cultivation technology is a part of the sugarcane intensification programs to supply the national sugar demand. Fertilization package is one component in of the of cultivation technology improvement. The research aims to obtain the information on (1) the role of Ca + Mg versus Sulfur nutrients, (2) the integration of low-dosage compound fertilizers with manure versus high-dosage compound fertilizers without manure, and (3) moderate-dosage versus very high-dosage of compound fertilizer without manure in improving productivity, sugar yield and economic benefits in sandy upland. The research was conducted in November 2012 - October 2013 at Asembagus Experimental Station, Situbondo, East Java. Four fertilizer packages was arranged in a Randomized Block Design and replicated three times. Data were analyzed by orthogonal contrast. The results showed that package of compound fertilizer containing Ca + Mg inccreased productivity (11,67%), sugar yield (15,51%) and economic benefit (293,3%) from the package of fertilizer without containing Ca + Mg with high-dosage Sulfur. Package of high-dosage compound fertilizer containing Ca + Mg without manure inccreased productivity (5.82%), sugar yield (8.26%) and economic benefit (54%) from package of low-dose fertilizer + manure. Package of very high-dosage compound fertilizer containing Ca + Mg inccreased productivity (32%), sugar yield (31,32%) and economic benefit (347,7%) from moderate-dosage fertilizer package.